The use of a combination of Diclofenac and Orphenadrine for analgesia in knee replacement - M. V. Kuzmina; I. V. Shlyk; V. A. Panafidina; A. A. Kozhevin; Yu. S. Polushin; V. O. Krivov (Вестник анестезиологии и реаниматологии)
The objective was to assess the effectiveness and safety of the use of a fixed combination of Diclofenac and Orphenadrine (Neodolpasse) for analgesia  in patients who underwent knee replacement.Materials and methods. 40 patients who underwent knee replacement in conditions of combined spinal-conduction analgesia (femoral nerve  block) were included into the study. In the main group(n = 20), Neodolpasse (a combination of Diclofenac 75mg and of Orphenadrine 30 mg in  250 ml of solution) was administered intravenously 30 minutes before surgery, and then in the postoperative period 2 times a day for 2 days. In the  comparison group (n = 20), Ketoprofen (intravenously,100 mg) was used instead of Neodolpasse 30 minutes before surgery, in the postoperative  period, it was continued 2 times a day for 2 days (intravenously, 100 mg). The severity of the pain was assessed with a visual analog scale (VAS) 6,  12, 24 and 48 hours after surgery. The assessment of the restoration of the supporting function of the operated leg and the ability of the patient to  perform active movements in the knee joint was carried out after 24 and 48 hours. The possible side effects was assessed throughout the entire period.Results. The median value of VAS after 24 hours in the main group was 2.5 (2;3) points, which was significantly lower in compassion to VAS of the  control group 4(3;5) p = 0.006. A more pronounced analgesic effect while using Diclofenac and Orphenadrine persisted for 48 hours, the median  value of VAS in the main group after surgery was 2 (2;3), in the control group – 3 (2.8;4) p = 0.021. There were no significant differences in the  recovery time of restoration of the supporting ability of the operated leg and knee joint function, in the frequency of Tramadol use in the compared  groups. Side effects and complications were not identified.  Conclusion. The use of the fixed dose of Neodolpasse as part of multimodal perioperative analgesia in patients, who underwent knee replacement,  contributed to a decrease in the severity of pain syndrome in the postoperative period.